If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 6x + 4 = 5(3x + 8) Reorder the terms: 4 + 6x = 5(3x + 8) Reorder the terms: 4 + 6x = 5(8 + 3x) 4 + 6x = (8 * 5 + 3x * 5) 4 + 6x = (40 + 15x) Solving 4 + 6x = 40 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 4 + 6x + -15x = 40 + 15x + -15x Combine like terms: 6x + -15x = -9x 4 + -9x = 40 + 15x + -15x Combine like terms: 15x + -15x = 0 4 + -9x = 40 + 0 4 + -9x = 40 Add '-4' to each side of the equation. 4 + -4 + -9x = 40 + -4 Combine like terms: 4 + -4 = 0 0 + -9x = 40 + -4 -9x = 40 + -4 Combine like terms: 40 + -4 = 36 -9x = 36 Divide each side by '-9'. x = -4 Simplifying x = -4

| 5-11x=7(5-2x) | | -2(18-3x)=7x+2x | | 2(4x-12)+3x=6x+1 | | 12=16-4n | | 9(2+x)-4x=3x-10 | | 10x+7=8(2x-4)-9 | | 3(4x+1)-9x=6(2-x) | | 3x+10+5=-14 | | 6(1+3x)=-8(-2x+5)-4 | | 10-20a=-6-13a | | 10-20a=-6-12a | | 6x-(5x+5)=-8-2(x+12) | | 14+5n=-4n+17 | | 27-11x=x-33 | | -7x-2=24-9x | | 21x+6=17x-26 | | 11x=8x-6 | | 3+4x=9x+13 | | -x-29=13+2x | | -18+5x=-12x-1 | | 8-5w=-37 | | -9x-21=35-x | | 18-4v=42 | | 7x-2=-2x-29 | | N-20=5 | | 104=y-67 | | -4+t=-7 | | 36+15x=17x | | G+5=33 | | 19+p=6 | | 15=b-(-65) | | -15-4x=6-3x | | 12x-9=8x-37 | | -5x+40=6x-70 | | 16-5(3t-4)=8(-2t+11) | | -x-2=1-2x | | 21-n=-8 | | 7(7c+1)-4c=13(3c-2) | | 3q-16q=7+2(-8q-3) | | 44=t-72 | | 3(2p+7)=15(p-4) | | P+(-26)=16 | | 19=c+12 | | 12(5+2y)=4y-(6-9y) | | N+23=4 | | -67=11+k | | 18-(-f)=91 | | 14-3(5t-12)=1-(20t+1) | | 88=125-(-u) | | 5x-2=4x | | 2x+5=-21 | | 2x(x-2)=54 | | 4x-4=4x+2 | | x+x(x-2)=54 | | 3c+4=-20 | | 3h+4=16 | | 2x+36+40=180 | | 9x-22=59 | | 11x+8=9x+14 | | 4x+52=9x+14 | | 4x+52=9x+12 | | 11x-10=7x+2 | | 5x+28=13x-44 | | 5x-3=13x-59 | | 4+4x=34+x |